Recurrent Thymoma-Associated Paraneoplastic Encephalitis Resulting From Multiple Antibodies: A Case Report. (April 2020) - Safadi, Amy Li; Wang, Tian; Maria, Gianluca Di; Starr, Amy; Delasobera, Bronson E.; Mora, Carlos Alberto; Tornatore, Carlo
Few reports describe the clinical course and acute-care management of patients with recurrent multi-antibody paraneoplastic encephalitis. We describe a rare case of a patient having thymoma with multiple paraneoplastic syndromes who was found to have antibodies to α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) followed by N -methyl-d -aspartate (NMDA) receptor in the setting of residual thymic tissue. He initially presented to the hospital with severe, rapidly progressive encephalitis with simultaneous antibodies to AMPA and voltage-gated potassium channel complex receptor. Brain magnetic resonance imaging revealed scattered white matter hyperintensities and an enhancing lesion adjacent to the left caudate. Computerized tomography showed an anterior mediastinal mass that was resected and revealed to be a thymoma. He was refractory to treatment with intravenous immunoglobulin, high-dose steroids, and plasmapheresis. He was then started on monthly cyclophosphamide. After 3 cyclophosphamide infusions, he began to show improvement in his alertness, ability to speak, and capacity to follow commands. One month later, he was readmitted to the hospital for new and unusual behavioral outbursts and agitation. He was found to have new anti-NMDA receptor antibodies in his cerebrospinal fluid in the setting of residual hyperplastic thymic tissue that required another resection. He was treated with rituximab and then cyclophosphamide (due to an infusion reaction with rituximab) with positive outcomes. The presence of multiple antibodies may be associated with poor prognosis, requiring prompt recognition and aggressive immunosuppressive treatment. New neurological symptoms should prompt a search for residual pathologic tissue or tumor recurrence causing new autoantibodies and additional paraneoplastic syndromes.